The Normative Definitions of Inclusive Education Developed by Teachers from Numerous Schools and of Varied Professional Experience - Wanda Baranowska; Justyna Leszka (Nicolaus Copernicus University in Toruń, 2019)
The purpose of the research as presented by us in this article, was to determine the aims with which teachers from various types of schools and of varied professional experience develop normative definitions of inclusive education. We paved the way to formulate these aims in the research tool with the analysis of literature on the subject, demonstrating three main trends in defining inclusive education. One hundred and eighty-eight teachers were surveyed, providing answers to the following research questions: 1/ domination of aims in definitions being developed and 2/ their correlations with professional experience and place of employment. We subjected them to a quantitative and correlational analysis. As a result, we determined that the aims related to meeting the needs of students with developmental disorders and those at risk of educational exclusion amongst the teacher definitions of inclusive education are dominant. In fact, the aims of the "every school for every student" idea of optimal inclusion are virtually missing. We determined that in the subject group, the type of school, teacher employment as well as their professional experience is related to the definition being developed.